2018
DOI: 10.1093/jas/sky157
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for bone strength in laying hens1

Abstract: Bone fracture in egg laying hens is a growing welfare and economic concern in the industry. Although environmental conditions and management (especially nutrition) can exacerbate it, the primary cause of bone weakness and the resulting fractures is believed to have a genetic basis. To test this hypothesis, we performed a genome-wide association study to identify the loci associated with bone strength in laying hens. Genotype and phenotype data were obtained from 752 laying hens belonging to the same pure line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Although some report QTL on chromosome 1, these do not appear to coincide with the QTL that we finemapped in this study [61,62]. Using a genome-wide association approach in one of the populations in this study, loci with a larger effect than the CBS loci have been observed, which suggests we can make progress in finding the underlying mechanism for these loci if large enough samples can be assembled [63].…”
Section: Discussionmentioning
confidence: 61%
“…Although some report QTL on chromosome 1, these do not appear to coincide with the QTL that we finemapped in this study [61,62]. Using a genome-wide association approach in one of the populations in this study, loci with a larger effect than the CBS loci have been observed, which suggests we can make progress in finding the underlying mechanism for these loci if large enough samples can be assembled [63].…”
Section: Discussionmentioning
confidence: 61%
“…To summarize, there are clear genetic effects on bone quality, which can be supported by a number of direct studies in addition to between-breed studies already mentioned ( Bishop et al., 2000 ; Dunn et al., 2007 ; Podisi et al., 2012 ; Eusemann et al., 2018a ; Raymond et al., 2018 ). There are some studies that seem to corroborate the role of AFE in bone quality, but it must also be recognized that a number of studies do not show effects.…”
Section: Additional Explanations For Kbf Susceptibilitymentioning
confidence: 99%
“…PRKAR2B is the most abundant regulatory subunit in endocrine tissues. Previous endeavours have demonstrated that mutations of PRKAR2B are associated with (Kerkhof et al, 2010) and with bone strength in laying hens (Raymond, 2016). NR2F2 and RIMS2 have been scarcely investigated in livestock.…”
Section: Candidate Genes For the Trait Of Bone Weightmentioning
confidence: 99%
“…NR2F2 is a member of the nuclear receptor superfamily, which is widely expressed in the mesenchymal compartment of developing tissues and organs including the heart, blood vessels, muscles and limbs. NR2F2 was reported to induce adipogenic differentiation and suppress osteoblastic differentiation (Raymond, 2016). RIMS2, which codes for a presynaptic active zone protein that regulates synaptic vesicle exocytosis of neurotransmitters, plays an important role in controlling bone remodelling through stimulation, maturation and differentiation of osteoblasts and osteoclasts.…”
Section: Candidate Genes For the Trait Of Bone Weightmentioning
confidence: 99%